2006
DOI: 10.1590/s1516-89132006000600003
|View full text |Cite
|
Sign up to set email alerts
|

Identification and colonization of endophytic fungi from soybean (Glycine max (L.) Merril) under different environmental conditions

Abstract: A total of 297 endophytic fungi were isolated from 1728 leaf and stem fragments collected about twenty and forty days after germination from soybean (Glycine max (L.) Merril) plants grown in the field and a greenhouse. The fungi belonged to eight groups, six dematiaceous genera (Alternaria, Cladosporium, Chaetomium, Curvularia, Drechslera and Scopulariopsis) and the non-dematiaceous genera Acremonium, Aspergillus, Colletotrichum, Fusarium, Paecilomyces and Penicillium along with some Mycelia sterilia.. There w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
42
0
10

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 21 publications
6
42
0
10
Order By: Relevance
“…This autoregulatory mechanism occurs through long-distance signaling between the shoot and root (30). To date, several studies of soybean-associated microbial communities have been reported (13,20,33,35). However, whether bacterial endophytes use systems similar to those used by rhizobia and mycorrhizal fungi in their associations is largely unknown (32).…”
mentioning
confidence: 99%
“…This autoregulatory mechanism occurs through long-distance signaling between the shoot and root (30). To date, several studies of soybean-associated microbial communities have been reported (13,20,33,35). However, whether bacterial endophytes use systems similar to those used by rhizobia and mycorrhizal fungi in their associations is largely unknown (32).…”
mentioning
confidence: 99%
“…Aspergillus has rarely been reported as leaf endophyte, but this work resulted that this species as leaf endophyte of chili and proven by colonization test. The role of Aspergillus as leave endophyte has been reported in soybean and neem trees (Pimentel et al 2006;Verma et al 2007). Other fungal endophytes isolated in this study were Coniothyrium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Jamur ini dapat diisolasi pada hampir semua bagian tanaman yang tumbuh di daerah tropis dengan iklim yang berbeda (Laran et al, 2002). Jamur endofitik lebih banyak diperoleh dari isolasi tanaman yang berada di lapangan dibanding tanaman yang ada di rumah kaca (Pimentel et al, 2006). Salah satu jamur endofitik yang sering ditemukan dan mampu berperan sebagai agens pengendali hayati yaitu Trichoderma spp.…”
Section: Pendahuluanunclassified